Key Stakeholders Perceptions of Assistive Technology to Support People with Dementia living at home. - Keogh, Brian; Daly, Louise; Brady, Anne-Marie; Hynes, Geralyn; Mc Carron, Mary (My University, 2018)
Background: The use of assistive technology (AT) to support people with dementia to live well at home has gained increasing attention. During two pilot projects, AT packages were provided as part of enhanced community supports for people living with dementia. The authors were commissioned to evaluate the pilot projects. Aim: The aim of this presentation is to discuss the findings in relation to key stakeholders perceptions of the use of assistive technology for people with dementia living at home. Methods: The findings are drawn from the qualitative arm of the evaluation. Interviews were conducted with people with dementia and family carers, and individual interviews and focus groups were held with service providers. Seventeen people with dementia and their family carers (n=17), and fifty-eight (n=58) service providers took part across the two project sites. Findings: The assistive technology included fall detectors, smoke detectors, carbon monoxide detectors, bed occupancy sensors, pillow alerts, personal alarms, and property exit sensors.There was a mixed reaction to the AT. In one project site, uptake was less than anticipated, as it was not perceived as useful given the person with dementia’s individual needs at that particular time. There were also reports of confusion as to the role of the AT and a lack of knowledge about how to use it by people with dementia. There were some positive reports with family carers suggesting that the technology provided some peace of mind. Service providers noted that applications for AT involved excessive paperwork and were sometimes unsuccessful. Conclusion: Under-utilisation of AT may have occurred because the technology provided was inconsistent with the wants, needs or abilities of those it was provided to. The range of AT provided emphasised safety. More appropriate options may have been considered in light of individual needs given their stage in the dementia journey.
28th Alzheimer Europe Conference: Making dementia a European priority .
Keywords: Assistive Technology (AT); Dementia